The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0096887
|View full text |Cite
|
Sign up to set email alerts
|

No Chemopreventive Effect of Nonsteroidal Anti-Inflammatory Drugs on Nonmelanoma Skin Cancer: Evidence from Meta-Analysis

Abstract: BackgroundNonmelanoma skin cancer (NMSC),which includes squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), is the most common form of cancer, and its incidence is increasing. Nonsteroidal anti-inflammatory drugs (NSAIDs) have been reported to be chemopreventive for NMSC. However, the results from published studies were controversial.MethodsWe searched the PubMed and Embase databases for relevant studies. Moreover, relevant reviews regarding the use of NSAIDs for NMSC patients were examined for poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
0
31
0
2
Order By: Relevance
“…Whether an agent is a good chemoprophylactic candidate is determined by the risk : benefit ratio. Many agents, such as beta carotene, selenium, synthetic retinoids (tretinoin, isotretinoin) and nonsteroidal anti‐inflammatory drugs have been tested but showed no chemopreventive effect on BCC development . However, when retinoids were used in patients with genodermatoses (NBCCS, XP) a more promising protective effect was seen on BCC development .…”
Section: Preventionmentioning
confidence: 99%
“…Whether an agent is a good chemoprophylactic candidate is determined by the risk : benefit ratio. Many agents, such as beta carotene, selenium, synthetic retinoids (tretinoin, isotretinoin) and nonsteroidal anti‐inflammatory drugs have been tested but showed no chemopreventive effect on BCC development . However, when retinoids were used in patients with genodermatoses (NBCCS, XP) a more promising protective effect was seen on BCC development .…”
Section: Preventionmentioning
confidence: 99%
“…Systematic reviews, including observational studies and a randomized clinical trial, have assessed the association between aspirin and nonaspirin NSAID use and KC . Muranushi et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the development of skin cancer, there has been conflicting evidence regarding the chemopreventive role of NSAIDs (Asgari, Chren, Warton, Friedman, & White, ; Elmets, Ledet, & Athar, ; Muranushi, Olsen, Pandeya, & Green, ; Zhang, Liang, Ye, & Wang, ). A case‐control study of 415 patients (43–85 years of age) diagnosed with SCC in the Kaiser Permanente Northern California population matched on age, gender, and race with 415 control subjects found no associations between the use of aspirin or other NSAIDs (self‐reported regular use or pharmacy data) and SCC risk (Asgari et al, ).…”
Section: Nsaids As Chemopreventive Agentsmentioning
confidence: 99%
“…A case‐control study of 415 patients (43–85 years of age) diagnosed with SCC in the Kaiser Permanente Northern California population matched on age, gender, and race with 415 control subjects found no associations between the use of aspirin or other NSAIDs (self‐reported regular use or pharmacy data) and SCC risk (Asgari et al, ). A subsequent meta‐analysis of data from eight studies (seven observational studies and one randomized controlled trial) investigating the effects of NSAIDs on nonmelanoma skin cancers (NMSCs) found no significant differences between users and nonusers of NSAIDs in their risk of developing SCC (relative risk [RR] = 0.86 [95% CI 0.73–1.02], p = .085) or basal cell carcinoma (BCC) (RR = 0.94 [95% CI 0.85–1.04], p = .266) (Zhang et al, ). In contrast, evidence from several preclinical, epidemiological, and translational studies has suggested that COX‐2 inhibitors could have potential in preventing NMSC development (Elmets et al, ).…”
Section: Nsaids As Chemopreventive Agentsmentioning
confidence: 99%